Astyanax pynandi sp. n. (Characiformes, Characidae) from the Esteros del Iberá wetland, Argentina - Casciotta, Jorge Rafael (2003)
Astyanax pynandi is described from the Esteros del Iberá, one of the major wetlands in South America. Astyanax, pynandi bears hooks on all fin rays of males, such as in A. troya and A. ojiara. Astyanax pynandi is distinguished from the remaining species of the genus by the following combination of characters: one maxillary tooth with 5 or 7 cusps; teeth of inner premaxillary row expanded distally; low dentary, bearing 8 teeth decreasing in size anteroposteriorly; 34-37 perforated scales in lateral series; 6-7 upper transverse scales; iii-v, 21-26 anal-fin rays; orbital diameter (36.7-43.5% of HL); postorbital length (37.0-44.7% of HL); and peduncle length (32.3-37.7% of HL). One humeral spot vertically elongated, bounded by a light area, and a second lateral spot faint or well developed.